Currículo e construção da identidade Karipuna na Aldeia Manga, Amapá - Fonseca, Mary Gonçalves (2019)
This thesis is about Jorge Iaparrá Indigenous State School’s curriculum. It relates its cultures, identities and knowledge to the Karipuna’s identity project of Manga’s Village, located in Uacá’s Indigenous Territory, at Oiapoque’s County, Amapá State, wich borders French Guiana. It’s a study about the school’s role in strenghtening the identity of a people who define themselves as mixed Indians, analyzing factors as social, polictical and cultural ones which permeate the pedagogical practice, as well as the fragilities and contradictions that represent risks to the indigenous subjects, in order to construct an emancipatory school’s education. This society’s historical processes reveal victims’ communities that remodeled themselves around an identity project, begotten by a manifold of other ones, ruled out and expropriated from their equality, as well as contrasts, rights. These days, the indigenous rework their cultures, as well as share social bonds which anchor community life, in a universe of meanings and particular ways of being in the world, and also facing different worldviews. The school, as a social project, is part of their well-living plans, which links networks of mutuality, woven around the Karipuna and societies at the region, known as Indigenous Peoples of Oiapoque. Studies carried out at the school point to distinct conceptions: school as an ideologica front, and the one ressignified by indigenous people during culture’s reprocessing. This work places emphasis on curriculum issues, and their connections with power relations, which represent weakness or threats to Karipuna’s corporate projects. A school’s curriculum is never neutral: it’s a locus of mediations creating an organizational culture which influences the learning community. It can also be a resistance and struggle for social justice’s place. The ethnographic method was used to describe and support the school context’s reality, for a consistent description according to Geertz. I especially base this work on theoretical-critical formulations from Enrique Dussel and Paulo Freire, expecting that it generates reflections that stimulate pedagogical practices, that have curricular justice on the horizon